Rodzice uczniów kształcących się w klasach integracyjnych – ich motywy i oczekiwania - Przybyszewska, Dominika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
Integrated classes are one of the possible forms of education student with a disability. They are considered as an alternative to mass classes and special classes. Opinions about their functioning are often different. Also, there are a variety of reasons for choosing this form of education for the child. The article presents the results of a survey among parents of children studying in integrated classes in the city of Poznan. The aim was ascertain the reasons for parents to choose schools inclusive; getting to know the parents' expectations and to determine the degree of their fulfillment.